2018
DOI: 10.1073/pnas.1808320115
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Sprouty 1 and 2 enhances survival of effector CD8 + T cells and yields more protective memory cells

Abstract: Identifying novel pathways that promote robust function and longevity of cytotoxic T cells has promising potential for immunotherapeutic strategies to combat cancer and chronic infections. We show that sprouty 1 and 2 (Spry1/2) molecules regulate the survival and function of memory CD8 T cells. Spry1/2 double-knockout (DKO) ovalbumin (OVA)-specific CD8 T cells (OT-I cells) mounted more vigorous autoimmune diabetes than WT OT-I cells when transferred to mice expressing OVA in their pancreatic β-islets. To deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 105 publications
(163 reference statements)
1
31
0
Order By: Relevance
“…Furthermore, the importance of Sprouty expression appears to be dependent on oncogenic Ras mutations in certain tumors . In addition, the expression of the Sprouty/Spred family in CD8 + T cells might contribute to the suppression of antitumor immunity . Therefore, when the Sprouty/Spred family is targeted in cancer therapy, these should be taken into consideration to avoid unexpected results of the targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the importance of Sprouty expression appears to be dependent on oncogenic Ras mutations in certain tumors . In addition, the expression of the Sprouty/Spred family in CD8 + T cells might contribute to the suppression of antitumor immunity . Therefore, when the Sprouty/Spred family is targeted in cancer therapy, these should be taken into consideration to avoid unexpected results of the targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…29 It has recently been reported that the loss of Sprouty1 and Sprouty2 promotes the survival of effector CD8 + T cells, resulting in the formation of more protective memory CD8+ T cells. 30 Another study has shown that Spred1 is upregulated in CD8 + tumorinfiltrating lymphocytes in a TGFβ-dependent manner. 31 These findings implicate the Sprouty/Spred family as the new potential targets in cancer immunotherapy.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…Studies interrogating the regulation of TCRcoupled intracellular signaling pathways have provided important insight into the mechanisms controlling T cell activation, function, and effector and memory fate decisions. In PNAS, Shehata et al (2) demonstrate that the signaling molecules Sprouty 1 and Sprouty 2 (Spry1/2) antagonize TCR-mediated signaling through Akt-FoxO1/3a and limit CD8 + MP and subsequent memory formation ( Fig. 1).…”
mentioning
confidence: 99%
“…To date, the role of the Spry proteins in CD8 + effector T cell (Teff) responses and memory development is unknown. Shehata et al (2) show that the genes encoding Spry1 and Spry2, but not Spry3 and Spry4, are up-regulated in activated CD8 + T cells and memory subsets, suggesting that Spry1/2 may be the critical regulators of CD8 + T cells. To begin investigating the role of Spry1/2 in CD8 + Teff responses, Shehata et al induced type 1 diabetes in rat insulin promotermembrane-bound ovalbumin (mOVA) mice, which express OVA protein on pancreatic cells, by the adoptive transfer of naïve OVA-specific (OT-I TCR transgenic) CD8 + T cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation